Effects of a novel rice-based diabetes-specific formula on postprandial glucose and gastrointestinal hormones: a double-blinded multi-arm randomized crossover trial - Chaiyakul, Supat; Ketkham, Narong; Chaichana, Chartchai; Khumkhana, Nanta; Deekum, Wanjan; Wongshaya, Pakwuan; Suwanmalai, Thaniya; Hutchinson, Carol; Pramyothin, Pornpoj (Frontiers in Endocrinology, 2023)
Introduction: Rice is the main staple food in Thailand. We developed a novel rice-based medical food for diabetes (MFDM) powder formula, sourcing ingredients locally to reduce cost and improve availability for patients. Purpose: The goals of this study were to 1) measure the glycemic index (GI) and glycemic load (GL) of the MFDM powder formula in healthy individuals, and 2) assess postprandial glucose, insulin, satiety, hunger, and gastrointestinal (GI) hormone responses in adults living with prediabetes or early type 2 diabetes after consuming MFDM in comparison with a commercially available standard formula (SF) and a diabetes-specific formula (DSF). Methods: In Study 1, glycemic responses were assessed using the area under the curve (AUC), which was used to calculate GI and GL. Study 2 was a double-blinded multi-arm randomized crossover trial enrolling participants with either prediabetes or type 2 diabetes of ≤6 years. At each study visit, participants consumed either MFDM, SF, or DSF which contained 25 g of carbohydrates. Hunger and satiety were assessed using a visual analog scale (VAS). Glucose, insulin, and GI hormones were assessed using AUC. Results: All participants tolerated the MFDM well with no adverse events. In Study 1, the measured GI was 39 ± 5.86 (low GI) and GL was 11 ± 1.69 (medium GL). In Study 2, glucose and insulin responses were significantly lower after MFDM compared with SF (p-value <0.01 for both), however, those responses were similar between MFDM and DSF. MFDM suppressed hunger, promoted satiety, stimulated active GLP-1, GIP, and PYY, and suppressed active ghrelin although these changes were similar to SF and DSF. Conclusions: MFDM had a low GI and a low-to-medium GL. In people living with prediabetes or early type 2 diabetes, MFDM elicited reduced glucose and insulin responses when compared with SF. Rice-based MDFM may be an option for patients who are at risk for postprandial hyperglycemia.